2012
DOI: 10.1128/jvi.06874-11
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Utilization of Human Immunodeficiency Virus Type 1 Genomic RNA Is Not Dependent on a Nuclear Interaction with Gag

Abstract: In some retroviruses, such as Rous sarcoma virus and prototype foamy virus, Gag proteins are known to shuttle between the nucleus and the cytoplasm and are implicated in nuclear export of the viral genomic unspliced RNA (gRNA) for subsequent encapsidation. A similar function has been proposed for human immunodeficiency virus type 1 (HIV-1) Gag based on the identification of nuclear localization and export signals. However, the ability of HIV-1 Gag to transit through the nucleus has never been confirmed. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 69 publications
4
40
1
Order By: Relevance
“…Two studies in the past year confirmed that HIV-1 Gag lacks a CRM1-dependent nuclear export signal (2,18). In addition, HIV-1 Gag lacking the reported nuclear import and export signals can mediate efficient packaging (18). Our present results with HIV-1 Gag support the current consensus that a nuclear function of this protein in assembly can be excluded unless this occurs at a level that is below the detection limits of present methodologies.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Two studies in the past year confirmed that HIV-1 Gag lacks a CRM1-dependent nuclear export signal (2,18). In addition, HIV-1 Gag lacking the reported nuclear import and export signals can mediate efficient packaging (18). Our present results with HIV-1 Gag support the current consensus that a nuclear function of this protein in assembly can be excluded unless this occurs at a level that is below the detection limits of present methodologies.…”
Section: Discussionsupporting
confidence: 85%
“…3A to F, 4B, and 6C to F). The results suggest that (10,8,18,21,25,11,18, and 26 cells for the columns going from left to right, respectively), and the ratio of the MFI in the nucleus to the MFI in the total cell was determined and expressed as a percentage (mean Ϯ standard deviation). (K to Q) Subcellular localization of FIV MA-CFP, CA-CFP, and NCp2-CFP.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…An hRSV plasmid expressing the codon-optimized hRSV-F ectodomain fused to a His tag was transfected in 293T cells using polyethylenimine as described previously (4,37). Supernatants were harvested and placed on a column packed with 5 ml of cobalt resin (Thermo Scientific, Germany) as recommended by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…The initial recognition of the HIV-1 gRNA by Pr55 Gag , during which discrimination against cellular and spliced vRNAs takes place, occurs in the cytoplasm and involves a very limited number of Pr55 Gag molecules [42][43][44][45] . Once these complexes become anchored in the plasma membrane, Pr55 Gag molecules are rapidly recruited as viral particle assembly proceeds 43,46 .…”
mentioning
confidence: 99%